DESIGNING LMS AND CMS FOR CRITICAL LITERACY COURSE - Tara Mustikaning Palupi; Ilza Mayuni (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2023)
This second-year study which took place in 2022 aims to investigate, determine and design a learning management system (LMS) design through Moodle and Content Management System (CMS) through Google Sites for Critical Literacy course in Prodi Pendidikan Bahasa Inggris UNJ. Critical Literacy course aims to prepare the students to have the ability to interpret text critically and communicate actively in the multimodal context in a hybrid learning process. The study was conducted with the qualitative approach with The Successive Approximation Model (SAM) iterative phase research design. Throughout the Savvy Start and Iterative Design Phase, the phase rotated through design, prototype, and review to make sure students and lecturers can contribute and support the design direction. Forty-four students and one lecturer generates as participants in this study. Two kinds of modules were developed during the study, namely: (1) LMS on www.onlinelearning.unj.ac.id and (2) CMS on Google Sites. LMS and CMS modules for the Critical Literacy course were: (1) Defining Critical Literacy, (2) Literacy, Critical Literacy, Multi-literacy, Multimodal, (3) Data Literacy, Fact, and Hoax (4) Analyzing Multimodal Text (5) Reflective Notes (6) Mid-term Test (7) Analyzing Various Texts (8) Wrap Up (9) Final Semester Individual Project. These nine headings were categorized into four topics namely: Theories, Tests, Reflection, and Projects. The theories can be used to deliver learning materials and examples in the form of text, video, slides, QR codes, and websites. Meanwhile, the test could be used to provide assignments, exercises, and learning evaluations. Reflection was used to provide the students with opportunities to do both self- and peer-reflection on the learning processes. Finally, the projects were used to involve the students with problem-solving skills and self-regulated learning. The study’s findings showed that LMS and CMS could handle the complexity of teaching Critical Literacy in the digital environment. The Critical Literacy course should have attracted interest or participation from the students to familiarize, encourage, fulfill, assess, and comprehend the various texts. This LMS and CMS also provided students with class discussion, credible references, project-based activities, and criticism on literacy topics.